What price ecumenism? Divisions in the Church of England's approach to the 1952 Järvenpää Conference. Issue 2 (3rd April 2022) - Root, Terry
ABSTRACT: In 1933, ecumenical endeavour in the Church of England saw the creation of the Council on Foreign Relations, preceded four years earlier by Anglican theologians meeting informally with their counterparts from the Nordic Lutheran Churches. Following the Second World War these theological meetings resumed whilst official ecumenical meetings between the churches were sporadic and distinctions between the two confused. This article examines the Church of England's approach to the proposed 1952 theological conference in Finland. Correspondence between those who saw real value in these informal meetings and those who did not shines, a light on their ideological and bureaucratic differences. From that divisiveness, threats to end these conferences came from Archbishop Fisher and H. M. Waddams, General Secretary of the Council on Foreign relations, whilst Bishops Bell Hunter strove to protect them. This article argues their continuance was an important step on the road to the Porvoo Common Statement.